2003
DOI: 10.1177/095624780301500218
|View full text |Cite
|
Sign up to set email alerts
|

Alternate water supply arrangements in peri-urban localities: awami(people’s) tanks in Orangi township, Karachi

Abstract: Municipal water supply in Karachi has become grossly inadequate with reference to the user's needs and expectations. As a consequence of this inadequacy, communities suffer from the poor level of service. Peri urban locations, especially low-income settlements have very limited access to municipal water supply. Communities in these locations have to evolve alternate arrangements for acquiring the minimum quantities of water for human survival. In some situations, public sector agencies extend support in servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…This has been particularly prevalent in the monopoly supply of piped water, where documented experiences have shown that even where users attempt to exert power, or assert their right to participate in decision-making, these efforts can ultimately be stumped by the providers' capacity to turn off supply (O'Reilly and Dhanju, 2012). In other instances, even non-networked water vendors may periodically establish local oligopolies, and make arrangements with the official network provider to maintain the water scarcity that supports their power over consumers (Ahmed & Sohail, 2003;Mason et al, 2013;Swyngedouw 1995).…”
Section: (Ii) Monopoly Tendencymentioning
confidence: 96%
“…This has been particularly prevalent in the monopoly supply of piped water, where documented experiences have shown that even where users attempt to exert power, or assert their right to participate in decision-making, these efforts can ultimately be stumped by the providers' capacity to turn off supply (O'Reilly and Dhanju, 2012). In other instances, even non-networked water vendors may periodically establish local oligopolies, and make arrangements with the official network provider to maintain the water scarcity that supports their power over consumers (Ahmed & Sohail, 2003;Mason et al, 2013;Swyngedouw 1995).…”
Section: (Ii) Monopoly Tendencymentioning
confidence: 96%
“…Government policies have paid less attention to water supply in low-income settlements for reasons such as government mismanagement and conflict, absence of a legal mandate for network expansion in unplanned areas, lack of financial and community resources with the water utility to deliver services to the poor, neglect by statutory authorities and slum residents' ignorance of their rights and the water supply system (Devas & Korboe, 2000;Connors, 2005;Ahmed & Sohail, 2003;Hossain, 2012;Ghafur, 2000). These reasons lead to inadequate water supply in low-income settlements, requiring an external or internal stimulus to reform the top-down approach.…”
Section: Water Sectormentioning
confidence: 99%
“…Examples of such incentives include official development assistance (ODA) programmes with a focus on delivering services to the urban poor, unrest and dissatisfaction among the urban poor regarding the state of WSS services, and social pressure to include slum dwellers in participatory governance | 339 DEVKAR Et Al. (Ahmed & Sohail, 2003;Connors, 2005). Donors have influenced the delivery of water services in poor settlements by making funding contingent on taking legislative, institutional and technical measures to address the reasons for the poor state of service delivery.…”
Section: Water Sectormentioning
confidence: 99%
“…The collective action of the community is shaped by their "access to opportunities, poverty or wealth and sociocultural elements" (Oldfield, 2000: 869) that together they determine the spatial practice of the communities towards the place where they live. Unfortunately, such potential of collective action is often underestimated and people tend to depend on the formal intervention from the government rather than optimise their own capacity for actions (Ahmed and Sohail, 2003).…”
Section: Communal Toilet As a Collective Spatial Systemmentioning
confidence: 99%
“…There are "the 'potential energies' of groups act to transform and create new social spaces" (Borden et al, 2001: 17), suggesting that the space is produced and reproduced by the collective actions of the subjects. Collective action often becomes a community's way to generate solution to the problems in their living space, as demonstrated by various examples (Oldfield, 2000;Ahmed and Sohail, 2003;Inerfeld and Blom, 2002). The emergence of collective strategies is particularly prominent among the communities with some disadvantages -in terms of economics, spaces and access to services.…”
Section: Introductionmentioning
confidence: 99%